Adherence/Retention Alzheimer's Prevention Initiative Colombia Plan. Issue 1 (13th July 2018) - Rios‐Romenets, Silvia; Acosta‐Baena, Natalia; Lopez, Liliana; Madrigal‐Zapata, Lucia; Street, Helen; Jakimovich, Laura; Langbaum, Jessica B.; Cho, William; Reiman, Eric M.; Tariot, Pierre N.; Lopera, Francisco
Abstract: Introduction: The Alzheimer's Prevention Initiative Colombia Trial is a collaborative project involving the Neurosciences Group of Antioquia, Genentech/Roche, and the Banner Alzheimer's Institute, studying whether crenezumab can delay or prevent the clinical onset of Alzheimer's disease in cognitively unimpaired individuals who carry the PSEN1 E280A mutation. In an effort to optimize participant compliance and adherence and maintain interest in the trial for its duration, the Neurosciences Group of Antioquia developed an "Adherence/Retention Plan." This plan identifies potential barriers to trial adherence related to characteristics of the participants and study partners, protocol design, sponsors, investigators, environmental factors, and characteristics of this population in general and identifies potential solutions to these barriers. Methods: Neurosciences Group of Antioquia designed and implemented a number of strategies including a) a prescreening process that emphasized detailed and staged informed consent involving the participant and family and/or friends, b) a schedule of visits and assessments designed to minimize burden while achieving the trial's aims, c) appointment reminders, d) reimbursement for transportation and missed work, e) meals during study visits, f) birthday cards, g) quarterly newsletters, h) annual in‐person feedback meetings, i) a supplemental health plan to participants, and j) a social plan to support family members. All the methods used in this plan were approved by local ethics committees. Results: By the end of the fourth year of the trial, participant retention was 94.0%, with most participants reporting that they felt "very satisfied" with their participation in the trial. Discussion: The Adherence/Retention Plan plays a crucial role in maintaining adherence and compliance needed to achieve the ambitious goals of the Alzheimer's Prevention Initiative‐Colombia Autosomal Dominant Alzheimer's Disease Trial and may offer guideposts for other prevention trials.